'Men Don't Cry Over Women': Expressions of Love and Grief in Egyptian Popular Music. Issue 2 (1st December 2021) - Abdelazim, Ahmed
Abstract: By examining mahragānāt, a genre of music common among the low-income working class in Cairo, and upper-class pop music, this article studies the expression of love and grief across socio-economic classes in Egypt. It challenges the mainstream argument that men, especially those belonging to lower socio-economic classes, are expected to perform 'like men' and suppress their emotions and affection. These mahragānāt exhibit extreme affection and grief as men threat of inflicting self-harm or committing suicide if they lose their female lovers. This genre's popularity on social media resonates with increasing suicide rates among lower socio-economic classes due to failed love affairs. By focusing on expressions of love in Egyptian music, this article suggests a dialectic relation between love, class and the understanding of masculinity.